Curcumin supplementation ameliorates heat stress and affects early embryonic development - Ritika; Saini, Sudha; Shavi; Selokar, N L; Singh, M K (Animal Reproduction Update, 2024)
The temperature-humidity index (THI) is used to present the environmental factors causing heat stress. Heat stress’s effects on the effectiveness of reproduction have been extensively studied and reported. The length of endocrine state, estrus, follicular growth and development, fertilization, conception rate, uterine function, luteolytic processes, early embryonic development, and fetal growth have all been demonstrated that altered by heat stress. Heat stress is considered to cause oxygen-derived free radicals, or reactive oxygen species (ROS), such as hydrogen peroxide (H2O2) or superoxide anion, to be produced in oocytes/embryos, hence inducing oxidative stress. Antioxidants, both enzymatic and non-enzymatic, provide vital defense against oxidative damage caused by heat stress. Curcumin has anti-inflammatory, anti-cancer, anti-infectious, and antioxidant properties, it is widely used in many biological and medical fields. Curcumin uses this process to scavenge reactive oxygen species (ROS) and reactive nitrogen species (RNS) and when added to the culture media during in vitro culture, protect the embryos from ROS and encourage embryo growth as well as fetal development. This review aims to summarize the current knowledge on the role of curcumin during heat stress and embryonic development.